(untitled) (Scientific journal of the Fergana State University, 2024)
The increasing number of the world’s inhabitants leads to an increasing demand for meat products. Among the protein rich foods, fish products occupy a special place. That is why it becomes important to get high level of production from fish and what is more important is that it is necessary to protect fish from various diseases. The main objective is to study the species composition of helminths that cause harm to fish, to identify diseases, characteristics of harm by studying fish produced in reservoirs of Fergana valley. During the study the degree of harm of cestodes on 1 class, 2 detachments, 3 families, 3 generations, 3 species causing diseases in fish were found and studied.